2018
DOI: 10.1111/irv.12584
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human respiratory syncytial virus infection in people with acute respiratory tract infections in Africa: A systematic review and meta‐analysis

Abstract: AimThe epidemiology of human respiratory syncytial virus (HRSV) infection has not yet been systematically investigated in Africa. This systematic review and meta‐analysis are to estimate the prevalence of HRSV infections in people with acute respiratory tract infections (ARTI) in Africa.MethodWe searched PubMed, EMBASE, Africa Journal Online, and Global Index Medicus to identify observational studies published from January 1, 2000, to August 1, 2017. We used a random‐effects model to estimate the prevalence ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
18
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 86 publications
8
18
3
Order By: Relevance
“…Based on our study, RSV has a considerable contribution to the WPR as an aetiology of respiratory infection, especially in children less than 5 years. Our analysis of the difference in the RSV positivity rate between children under 5 years and greater than 5 years is concordant with the results from African region [10]. As the specific prevention measure of an RSV vaccine is not yet available, other respiratory infection prevention and control measures targeted at this age group should be implemented in both developed and developing countries.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Based on our study, RSV has a considerable contribution to the WPR as an aetiology of respiratory infection, especially in children less than 5 years. Our analysis of the difference in the RSV positivity rate between children under 5 years and greater than 5 years is concordant with the results from African region [10]. As the specific prevention measure of an RSV vaccine is not yet available, other respiratory infection prevention and control measures targeted at this age group should be implemented in both developed and developing countries.…”
Section: Discussionsupporting
confidence: 88%
“…The largest population group included in our RSV study is children with acute respiratory tract infections, 159 studies, which show a prevalence higher than the adult group. Our results are similar to previous systematic studies in both developing countries [9,10] and developed countries [43,44]. The prevalence of RSV in adults is still not well-established compared with studies of adult influenza infection and the limited number of studies in adults might contribute to the lower reported prevalence in this age population.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Nonetheless, rates of detection appear to vary largely between published studies from different regions of the world. A meta-analysis realized between 2000 and 2017 including 20 African countries reported a detection rate of 22.6 % among children under the age of 5 years [25]. Ogunsemowo et al .…”
Section: Discussionmentioning
confidence: 99%